A Study on Material Removal Rate in Powder-Mixed Electro-Discharge Machining Utilizing Integrated Experimental and Computational Fluid Dynamics Analysis - Nguyen Huu-Phan; V.S. Ganachari; Shailesh Shirguppikar; P.B. Gavali; S.S. Deshmukh; P.S. Jadhav; L. Selvarajan; Nguyen Duc-Toan; M.V. Pachore (Tribology in Industry)
Electric discharge machining (EDM) serves as a pivotal technique for the precision machining of materials known for their inherent difficulty in conventional cutting processes. Its capability to fashion blind slots and intricate features in conductive materials, otherwise challenging to fabricate using traditional methods, underscores its significance in modern manufacturing. The effectiveness of Electrical Discharge Machining (EDM) hinges upon a multifaceted interplay of electrical and non-electrical variables, encompassing parameters such as current, voltage, cycle time, and powder concentration. This study delves into the realm of EDM with a specific focus on Powder-Mixed Electro-Discharge Machining (PMEDM), aiming to comprehensively explore and optimize the material removal rate (MRR). The experimental investigation, conducted with and without the incorporation of conductive powder particles into the dielectric medium, scrutinizes the impact on MRR, thereby shedding light on the efficacy of powder integration in enhancing machining efficiency. Furthermore, the study ventures into the realm of computational fluid dynamics (CFD) to simulate and analyze the intricate dynamics of dielectric flow, powder particle behavior, and debris movement within the inter-electrode gap (IEG). These simulations serve as invaluable tools in elucidating the underlying mechanisms governing the machining process, providing insights into the intricate interplay between electrical discharges, fluid flow, and particulate dynamics. The synthesis of experimental data and simulation results reveals a strong correlation between the inclusion of powder particles in the dielectric medium and the enhancement of machining efficiency, particularly evident in the observed improvements in MRR. The consistency between experimental findings and simulation outcomes underscores the validity and robustness of the study's methodologies and conclusions. In essence, this research not only contributes to the advancement of understanding of PMEDM but also underscores the potential of integrated experimental and computational approaches in optimizing machining processes. By elucidating the intricate dynamics of powder-mixed EDM and its implications on material removal efficiency, this study paves the way for enhanced precision machining in various industrial applications.